Heart rate estimation using on-nail wearable photoplethysmography - Nur Alia Athirah, Mohtadzar; Ertan, Balaban; Christopher, Beach; Paul S., Taylor; Robert J., Horne; John C., Batchelor; Alexander J., Casson (2024)
—Heart Rate (HR) measurements in current wearables are mostly derived from photoplethysmography (PPG). PPG signals have been measured at various locations on the body, however, to date, limited studies have investigated wearable, reflective mode, PPG signals from the finger- and toe- nails. Being rigid surfaces, they may provide comparatively motion robust measurements compared to sensors placed on flexible and stretchable skin. Here, we present an on-nail wearable PPG sensor to estimate HR from nail locations in motionfree and motion-present recordings. We compare to commercial electrocardiogram (ECG) and pulse oximeter (PO) units for 20 participants. PPG HR estimation demonstrated strong correlations with the ECG estimated HR, with a root mean square error of 1.6 beats per minute (bpm) and 2.2 bpm, for finger and toenail locations respectively. During motion these figures increased to 5.6 bpm and 12.8 bpm. No substantial difference in accuracy was found across the skin tone of participants. These results demonstrate the potential feasibility of HR monitoring from nail locations. With sensors placed, for example, inside a shoe, this may offer very discrete monitoring for long term applications.